Prevalence and Risk Factors of Teenage Pregnancy at Burji District, Southwestern Ethiopia; Mixed Approach Study - Samuel Dessu Sifer; Abatalem Minlargeh Abere; Belete Worku (International Journal of Public Health)
ObjectivesIn Africa, the overall prevalence of adolescent pregnancy is 18.8%, with the sub-Saharan African region having a rate of 19.3%. The highest rates are found in East Africa at 21.5%, and in Ethiopia, the prevalence is even higher at 23.6%.MethodsA community-based cross-sectional explanatory sequential mixed approach study was carried out among 458 teenagers in Burji District from 15 January to 15 February 2024. A multistage systematic sampling technique for quantitative and purposive sampling for qualitative data was used. The quantitative data were collected through face to face interview using a structured and pretested questionnaire by trained data collectors while qualitative data were gathered through in depth interviews and focus group discussions. Variables with p-value less than 0.05 were declared as statistically significant.ResultsThe prevalence of teenage pregnancy was 21.8% (95% CI: 18.0, 26.0). Factors associated with teenage pregnancy included rural residence (AOR: 3.68; 95%CI: 1.29, 10.44), being married (AOR: 2.75; 95%CI: 1.06, 7.15), not using contraceptives (AOR: 5.75; 95%CI: 2.22, 14.86), and not discussing reproductive health issues (AOR: 2.60; 95%CI: 1.04, 6.76). In addition, the qualitative study identified lack of education and access to resources, social and relationship influences, cultural influences and economic and future outlook as a common cause of teenage pregnancy.ConclusionsConsequently, there is a high prevalence of teenage pregnancy in the area. Furthermore, place of residence, marital status, contraceptive use, and discussions about reproductive health issues were identified as independent factors associated with teenage pregnancy.